Odpowiedź:
A
[tex] {(7 + x)}^{2} = 49 + 14x + {x }^{2} \\ {(y + 3})^{2} = {y}^{2} + 6y + 9 \\ {(a + 1)}^{2} = {a }^{2} + 2a + 1[/tex]
B
[tex] {(x - 9)}^{2} = {x}^{2} - 18x + 81 \\ {(y - 5)}^{2} = {y}^{2} - 10y + 25 \\ {(2x - 3)}^{2} = {4x - 12x + 9}^{2} [/tex]
C
[tex](x - 4)(x + 4) = \\ = {x}^{2} - 16 \\ (3x - 7)(3x + 7) = \\ = {9x}^{2} - 49 \\ (2x + 5)(2x - 5) = \\ = {4x}^{2} - 25[/tex]
Szczegółowe wyjaśnienie:
wzory wykorzystane w przykładach
[tex]{(a + b)}^{2} = {a}^{2} + 2ab + {b}^{2} \\ \\ ( {a - b)}^{2} = {a}^{2} - 2ab + {b}^{2} \\ \\ (a + b)(a - b) = {a}^{2} - {b}^{2} [/tex]